Proceedings of the 2014 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2014
DOI: 10.3115/v1/d14-1211
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Power: How Gender and Gender Environment Affect Manifestations of Power

Abstract: We investigate the interaction of power, gender, and language use in the Enron email corpus. We present a freely available extension to the Enron corpus, with the gender of senders of 87% messages reliably identified. Using this data, we test two specific hypotheses drawn from the sociolinguistic literature pertaining to gender and power: women managers use face-saving communicative strategies, and women use language more explicitly than men to create and maintain social relations. We introduce the notion of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Prabhakaran et al (2012Prabhakaran et al ( , 2014b used indicators of overt displays of power (ODPs) that place constraints on the recipient (e.g., "come to my office now") to identify power dynamics within the corporate email communications of top Enron executives. Indicators were obtained using a supervised model trained on manual annotations and revealed that male superiors used significantly more ODPs compared to male and female subordinates and that female superiors used the least ODPs of all.…”
Section: Social Relationships Through the Process Of Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prabhakaran et al (2012Prabhakaran et al ( , 2014b used indicators of overt displays of power (ODPs) that place constraints on the recipient (e.g., "come to my office now") to identify power dynamics within the corporate email communications of top Enron executives. Indicators were obtained using a supervised model trained on manual annotations and revealed that male superiors used significantly more ODPs compared to male and female subordinates and that female superiors used the least ODPs of all.…”
Section: Social Relationships Through the Process Of Communicationmentioning
confidence: 99%
“…Another approach to power measurement uses message control. Prabhakaran et al (2014b) analyzed US presidential primary debates to identify speaker turns when conversation changed from one topic to another. Higher-powered candidates-those posting higher poll numbers-were less likely to shift topics during the course of the debate, suggesting that control of the conversation is a consequence of electoral popularity.…”
Section: Social Relationships Through the Process Of Communicationmentioning
confidence: 99%
“…Even for "conventional" digital documents, we know, at least in the UK civil service, registries and file plans have all but vanished (Allan, 2014(Allan, , 2015. The Enron emails that were made available during the legal investigations into the business consisted of 620,000 assorted emails and the only way that sense could be made of them was by using advanced computational and statistical techniques at the Language Technology Institute at Carnegie Mellon University (Klimt and Yang, 2004b) and in the Department of Computing Science at Columbia University (Prabhakaran et al, 2014). Such techniques are now becoming common in the digital forensics community (in commercial tools such as Nuix) 1 Their potential for application to the archival material would arguably only be a sophisticated extension in the digital world to the fundamental concept of cataloging (TNA, 2016).…”
Section: The Challenge Of the Newmentioning
confidence: 99%
“…A closely related area of research has been predicting power relations in dialog Danescu-Niculescu-Mizil et al, 2012;Strzalkowski et al, 2013;Prabhakaran et al, 2014b;Prabhakaran and Rambow, 2013]. This can include several types of power relationships, such as hierarchical and administrative power, as well as influence.…”
Section: Influence In Social Networkmentioning
confidence: 99%